Analysis of the spatial distribution of road accidents attended by the Mobile Emergency Service (SAMU-192) in a municipality of northeastern Brazil - Cristine Viera do Bonfim; Aline Galdino Soares da Silva; Weinar Maria de Araújo; Carmela Alencar; Betise Mery Alencar Furtado (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2018)
This study describes the epidemiological characteristics of road accident victims attended by the Brazilian Mobile Emergency Service (SAMU-192) and located in the areas of highest accident density in the municipality of Olinda, (Pernambuco, Brazil). Kernel density estimation was used to detect spatial agglomerations of accidents. In 2015, 724 accidents occurred; of these, 73.48% of the victims were males aged 20-39 years. There was a predominance of accidents involving motorcycles (54.97%). Accident clusters were detected in the main traffic corridors, with run-over accidents located near bus terminals. Spatial analysis proved to be a relevant instrument for the identification of accident clusters and the application of effective prevention and traffic safety improvement measures.